Endurance Ability Of West Sumatera Football Players: Analysis Of Pon Players - Ridho Bahtra (STAMINA, 2026)
The problem of this research is the lack of empirical data regarding the endurance capabilities of West Sumatra PON soccer players based on sports science. The purpose of this study is to determine the endurance capabilities of West Sumatra PON soccer players. Endurance capability data is very important for coaches as a basis for developing measurable and structured training programs. This study uses a quantitative descriptive method with a survey approach. The sample in this study was 30 young soccer players. The instrument used was the intermittent recovery yoyo test. The collected data will be analyzed using statistical techniques with the help of SPSS 26 software and Microsoft Excel. The results of the data analysis revealed that the endurance capability (VO2max) of players who were in the low category was 1 person (3.33%), the poor category was 29 people (96.67%), and no one obtained a very good, good, fairly good, and moderate VO2Max. From these results, it can be concluded that the endurance capabilities of players still have not reached the standards required for professional soccer players. Coaches must improve the endurance capabilities of players to compete at a higher level. This data can be used as a reference for coaches in designing and developing more effective training programs to improve players' endurance capabilities.